STRATEGI PENDIDIKAN KARAKTER DALAM MENGATASI PERILAKU BULLYING DI MTS SULTAN AGUNG KALIPARE - Fai’s Zatul Azizah, Alif Achadah (JIPI (Jurnal Ilmiah Pendidikan Islam), 2026)
This study is motivated by the increasing cases of bullying in schools, which negatively impact students' character development. Although character education has been implemented in the Merdeka Curriculum, many students are still involved as perpetrators or victims of bullying. This study aims to analyze bullying behavior and explore character education strategies that can be applied to overcome it, particularly through values of empathy, responsibility, and the active involvement of teachers and the school environment. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The results show that physical and verbal bullying are the most common forms occurring at MTs Sultan Agung Kalipare. The strategies applied include giving advice, instilling religious values through Quranic and Kitab recitation activities, and anti-bullying socialization. This approach aims to build morality, strengthen faith, and create a safe and harmonious school culture.